The ‘Hindutvafication’ of Jammu & Kashmir: A Potential Nuclear Flashpoint in South Asian Region - Maliha Mughal (ASIAN Journal of International Peace & Security (AJIPS), 2025)
Over last seven decades, Kashmir conflict has evolved as a major issue of contention between Pakistan and India. Though both states have intermittently managed to strike breakthroughs through dialogue and negotiations; with Bharatiya Janata Party led government ruling India, the political and demographic landscape of Jammu and Kashmir has continued to deteriorate since 2014. After the revocation of Articles 370 and 35-A of Indian Constitution in 2019, Modi administration has reportedly issued a substantial number of domicile certificates to non-residents Hindus for converting the in to a Hindu dominated region. This study analyzes the ideological concept of Hindutva and its implementation by Modi government in Indian illegally occupied Jammu and Kashmir (IIOJK), its impacts on regional security and its evolution as a nuclear flashpoint between Pakistan and India. Using a qualitative approach based on secondary data, the paper also evaluates policy shifts, demographic transformations, strategic competition and bilateral tensions between India and Pakistan.